A Heartfelt Approach: On and Beyond Neoliberalism. (June 2016) - McElhinny, Bonnie
Abstract: Scholars analyzing neoliberalism have a two‐pronged challenge, since "neoliberalism" is both too little, and at moments too extensively, used in applied linguistics and sociolinguistics (see also Allan and McElhinny, n.d.). This article considers what the contributions to this special issue contribute towards the study of neoliberalism with a focus on emotional pedagogies, as it considers where and how the articles also show contestations of and challenges to neoliberalism.